Impact of Age on Retention in Care and Viral Suppression. (1st April 2015) - Yehia, Baligh R.; Rebeiro, Peter; Althoff, Keri N.; Agwu, Allison L.; Horberg, Michael A.; Samji, Hasina; Napravnik, Sonia; Mayer, Kenneth; Tedaldi, Ellen; Silverberg, Michael J.; Thorne, Jennifer E.; Burchell, Ann N.; et al.
Abstract : Background: Retention in care is important for all HIV-infected persons and is strongly associated with initiation of antiretroviral therapy and viral suppression. However, it is unclear how retention in care and age interact to affect viral suppression. We evaluated whether the association between retention and viral suppression differed by age at entry into care. Methods: Cross-sectional analysis (2006–2010) involving 17, 044 HIV-infected adults in 14 clinical cohorts across the United States and Canada. Patients contributed 1 year of data during their first full-calendar year of clinical observation. Poisson regression examined associations between retention measures [US National HIV/AIDS Strategy (NHAS), US Department of Health and Human Services (DHHS), 6-month gap, and 3-month visit constancy] and viral suppression (HIV RNA ⩽200 copies/mL) by age group: 18–29 years, 30–39 years, 40–49 years, 50–59 years, and 60 years or older. Results: Overall, 89% of patients were retained in care using the NHAS measure, 74% with the DHHS indicator, 85% did not have a 6-month gap, and 62% had visits in 3–4 quarters of the year; 54% achieved viral suppression. For each retention measure, the association with viral suppression was significant for only the younger age groups (18–29 and 30–39 years): 18–29 years [adjusted prevalence ratio (APR) = 1.33, 95% confidence interval (CI): 1.03 to 1.70]; 30–39 years (APR = 1.23, 95% CI: 1.01 to 1.49); 40–49 years (APR = 1.06, 95% CI: 0.90 to 1.22); 50–59 (APR = 0.92, 95% CI: 0.75 to 1.13); ≥60 years (APR = 0.99, 95% CI: 0.63 to 1.56) using the NHAS measure as a representative example. Conclusions: These results have important implications for improving viral control among younger adults, emphasizing the crucial role retention in care plays in supporting viral suppression in this population. Abstract : Supplemental Digital Content is Available in the Text.